Pengaruh Budaya Organisasai Terhadap Kinerja Pengurus Koperasi Unit Desa di Kabupaten Barito Kuala - Kinanti, Julitsa; Supriyanto, Supriyanto; Ratumbuysang, Monry Fraick Nicky Gillian; Rizky, Maulana (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to determine the effect of organizational culture on the performance of village unit cooperative administrators in Barito Kuala Regency. Descriptive quantitative research method with a sample of 37 administrators. Data collection techniques using observation, interviews, questionnaires and documentation. Data analysis using descriptive statistics, classical assumption analysis, simple regression analysis, hypothesis testing and the coefficient of determination. Based on the results of hypothesis testing that has been done, it shows that organizational culture affects performance. A good organizational culture can be achieved by implementing work rules that must be obeyed by all administrators, being thorough, results-oriented, establishing good cooperation between administrators, providing encouragement and assistance to fellow administrators and appreciating every achievement that has been successfully carried out.